Efektifitas Media Papan Penjumlahan Terhadap Peningkatan Hasil Belajar Matematika Siswa Kelas III SDN Wonotingal Semarang - Amanah, Dinda Tri; Januar, Henry; Poncowati, Lilik (STKIP Andi Matappa Pangkep, 2024)
The aim to be achieved in this research is to determine the effectiveness of using summation board media on student learning outcomes in class III students at SDN Wonotingal Semarang. This type of research uses the Classroom Action Research (PTK) method, which is carried out in two cycles using qualitative and quantitative descriptive analysis techniques. The research results show that using additional board media significantly improves student learning outcomes. The students' average score increased from 70 to 85 in the first cycle and to 90 in the second cycle. The results of this research indicate that the summation board media is effective in improving student learning outcomes and making learning more interesting and interactive.